Analisis Pola Konsumsi Pangan Rumah Tangga (Studi Kasus di Desa Kandang Kecamatan Tabir Kabupaten Merangin) - Is, Asnawati; Triani, Wahyu; Isyaturriyadhah, Isyaturriyadhah (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2021)
The study's goal was to evaluate food consumption trends based on quantity and quality and the factors that impact food consumption patterns. From March 10 to April 10, 2020, the research was conducted in Kandang Village, Tabir District, Merangin Regency, Jambi Province. The hamlet was purposefully chosen (purposive sample) because it has a somewhat vulnerable or priority food situation according to the 2019 Merangin Regency Food Security Service statistics. Lowest when compared to other villages or sub-districts in Tabir District. The data were examined using quantitative descriptive analysis and the Nutrition Adequacy Level (TKG) method, which included Energy Adequacy Levels (TKE) and Protein Adequacy Levels (TKP), to establish household food consumption patterns based on quantity. The Expected Food Pattern Analysis (PPH) purpose was to evaluate food consumption patterns based on quality factors. Meanwhile, multiple linear regression analysis was utilized to investigate the elements that impact food intake patterns. The quantity-based study of food intake findings demonstrates that the deficit category still dominates the household's Energy Adequacy Level (TKE), with an average consumption of 1000 to 1300 kcal/cap/day compared to the required nutritional adequacy rate of 2150 kcal/cap./hr. Meanwhile, the deficit group dominates the Protein Adequacy Level (TKP), accounting for 70% of the total with an average consumption of 19 to 38 g/cap/day of the necessary nutritional adequacy rate of 57 g/cap/day. After that, a PPH score of 83.2 was attained for the quality aspect, which was still below the optimum PPH score of 100. Furthermore, the factors that influence household food consumption patterns, as shown by the F test with a significant value of 0.016 and the t-test with a substantial weight of 0.001, include the number of family members.